THE RELATIONSHIP BETWEEN PARTICIPATION TO THE SCHOOL ADMINISTRATION AND ORGANIZATIONAL SILENCE PERCEPTIONS OF THE TEACHERS WORKING AT SECONDARY SCHOOLS (SAMPLE FOR TEKİRDAĞ PROVINCE) - Gizem ÇAKAL (Fırat University, 2019)
Codetermination is a provision of influencing decisions by involving those concerned in the process of taking managerial decisions. Organizational quietness is personnels’ withholding their views and concerns on organizational issues. The purpose of this research is to reveal relationship status between perceptions of teachers about participation in school administration and organizational quietness using the data on perceptions of teachers about participation in school administration and organizational quietness obtained from teachers, who work at secondary level schools in Tekirdağ province and its town centers in school year 2014-2015. For this purpose, the data has been gathered from 501 teachers, who are working at secondary education institutions in country towns and city center of Tekirdağ. As it aims to reveal the existing situation, relational screening method is used in this descriptive research. The data contains personal information sheet filled by the teachers, The Scale of Teachers’ Participation in the School Administration and The Scale of Organizational Quietness. On the process of analysis, Independent Two Samples t-Test and One Way Variance Analysis (One Way ANOVA) Test have been applied. In ANOVA test it has seen that there is a significant difference between samples. To determine which two samples have the difference, LSD Post Hoc Test has been applied. Pearson Correlation is used to determine the correlation between the scores of the scales and sub dimensions. According to the results of this research, it has been seen that teachers have high level of positive views on participation to the school administration (average score of The Scale of Teachers’ Participation in the School Administration is 3,71±0,39), and also it has been found that their perceptions on organizational silence behaviour are at mid level (average score of The Scale of Organizational Silence is 3,38±0,75). Correlational findings between Teachers’ Participation in the School Administration and Organizational Silence reveal that there is a significant and a weak negative relationship between teachers’ participation to the school administration and their organizational silence behaviours. Besides, it is determined that there is also a significant and a weak negative relationship between Teachers’ Participation to the School Administration and School Environment, Emotion and Source of Silence sub dimensions, and also between Codetermination Status sub dimension and Administrator and Isolation sub dimensions while there is a significant and moderate negative relationship between Codetermination Status sub dimension and School Environment, Emotion, Source of Silence sub dimensions and Organizational Silence in general. However, it is found that there is a significant and positive weak relationship between Benefits of Codetermination sub dimension and Administrator sub dimension, and also between Suggestions Improving Codetermination sub dimension and Emotion, Administrator and Isolation sub dimentions. But the findings show that there is a significant and positive moderate relationship between Factors Reducing Participation sub dimension and School Environment, Emotion, Source of Silence, Administrator, Isolation sub dimensions and Organizational Silence in general.